Design optimization of microfluidic channels for enhanced internal cooling in air-breathing silicon photovoltaic modules - Meena A.; Jaiswal A.; Jaiswal R.P. (My University, 2025)
Silicon photovoltaic (Si-PV) modules experience a substantial reduction in light conversion efficiency (LCE) due to solar heating. This study utilized our previously developed ‘internal’ cooling architecture, which incorporates microfluidic channels embedded in the rear EVA layer of Si-PV modules to bypass the thermal resistance of Tedlar backsheet, termed “air-breathing” Si-PV, (patent application no. 202211050095). However, the literature lacks guidelines for optimizing the internal cooling geometrical parameters to further improve their performance. This study focuses on optimizing geometrical parameters (dimensions and number density) of two channel geometries, rectangular and cylindrical, using a COMSOL model. Si-PV modules, air-cooled through internal channels of varied volume fractions (VFs), exhibited a temperature rise of only 12–15 °C, significantly lower than the 25 °C rise observed in conventional PV modules. Rectangular channels offered superior cooling relative to cylindrical channels, with additional temperature reductions of 1.93 °C, 1.36 °C, and 1.40 °C at VFs of 40 %, 50 %, and 60 %, respectively. This cooling advantage reduced the LCE loss from 16.75 % in conventional PV modules to 9.63 % and 8.34 % for cylindrical and rectangular channels, respectively, based modified air-breathing Si-PV modules (at a VF of 40 %), with rectangular channels achieving an additional 1.3 % improvement in LCE over cylindrical ones. © 2025 Elsevier Ltd